NATIONALISM INSIDE THE POEM OF â€œDIPONEGOROâ€ BY CHAIRIL ANWAR A HISTORICAL STUDY - Djojosuroto, Kinayati (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2014)
This study aims to reveal the meaning of the elements of nationalism in the poem "Diponegoro" by Chairil Anwar and to reveal the relationship between the poetry of "Diponegoro" with the history of Diponegoro War (Java War) in 1825 â€“ 1830. The "Diponegoro" poem is one of the phenomenal works that, if the contents are reviewed, alive and exist in a fighting spirit, the spirit of nationalism. In this postmodern era, the poetry of â€˜Prince Diponegoroâ€™ by Chairil Anwar is still exist as poem which fights for its country. The method used in this research is descriptive qualitative with content analysis techniques. Conclusion: 1. Poetry "DIPONEGORO" is the poem with struggling spirit. In this case, it was the fight of Diponegoro against the Netherlandsâ€™ colonialism. His nationalism, his love and obedience, his loyalty for his country, had led Diponegoro onto resistance because he wanted to liberate his people, from the domination and the grip of foreign power, the Netherlands. 2. The poem of â€œDiponegoroâ€ cannot be separated from the history of the past, the resistance of the people of Java against the Netherlandsâ€™ colonialism.